FROM CULTURE SHOCK TO CROSS-CULTURAL UNDERSTANDING IN READING COMPREHENSION: A RECEPTION STUDY OF FIFTH-SEMESTER EFL STUDENTS AT FTIK UIN DATOKARAMA PALU ON STEINBECK’S “THE PEARL” - Andi Muhammad Dakhalan; Ming Pong (Yayasan Adra Karima Hubbi, 2025)
Reading comprehension in EFL teacher education is increasingly framed as an ability to interpret texts critically, engage ethically with difference, and negotiate meaning across cultures. Yet, culturally distant literary texts often provoke affective disruption and moral discomfort that students may label as